2010
DOI: 10.1007/s12192-009-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel inducible cytosolic Hsp70 gene in Chinese shrimp Fenneropenaeus chinensis and comparison of its expression with the cognate Hsc70 under different stresses

Abstract: The heat shock protein 70 (Hsp70) family is widely expressed in eukaryotic cells as the major chaperone protein. In this study, the full-length complementary DNA (cDNA) of a novel inducible cytosolic Hsp70 family member (FcHsp70) was cloned from Fenneropenaeus chinensis. FcHsp70 full-length cDNA consists of 2,511 bp with a 1,890-bp open reading frame encoding 629 amino acids. Three Hsp70 protein family signatures, IDLGTTYS, IIDLGGGTFDVSIL, and IVLVGGSTRIPKVQK, were found in the predicted FcHsp70 amino acid seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 57 publications
2
29
0
Order By: Relevance
“…There are three characteristic motifs of the Hsp70s from the deduced amino acid sequence: signature 1 (9-16 aa, IDLGTTYS), signature 2 (197-210 aa, DLGGGTFD), and signature 3 (334-348 aa, IVLVGGSTRIPKIQK) by website search (http:// www.expasy.org) (Tabeta and Yamazaki, 2010). The other conserved motifs, such as two consecutive repeats of the tetrapeptide motif GGMP (Luan et al, 2010;Yang et al, 2010), the putative ATP-GTP binding domain, the putative bipartite nuclear location signal, and two cytosolic localization signals (a potential non-organelle eukaryotic consensus motif and the extreme C-terminal domain EEVD) (Shim et al, 2006;Tabeta and Yamazaki, 2010;Xie et al, 2010) were also identified (Fig. 2).…”
Section: Cloning and Sequence Analysis Of Turtle Thsc70mentioning
confidence: 99%
See 3 more Smart Citations
“…There are three characteristic motifs of the Hsp70s from the deduced amino acid sequence: signature 1 (9-16 aa, IDLGTTYS), signature 2 (197-210 aa, DLGGGTFD), and signature 3 (334-348 aa, IVLVGGSTRIPKIQK) by website search (http:// www.expasy.org) (Tabeta and Yamazaki, 2010). The other conserved motifs, such as two consecutive repeats of the tetrapeptide motif GGMP (Luan et al, 2010;Yang et al, 2010), the putative ATP-GTP binding domain, the putative bipartite nuclear location signal, and two cytosolic localization signals (a potential non-organelle eukaryotic consensus motif and the extreme C-terminal domain EEVD) (Shim et al, 2006;Tabeta and Yamazaki, 2010;Xie et al, 2010) were also identified (Fig. 2).…”
Section: Cloning and Sequence Analysis Of Turtle Thsc70mentioning
confidence: 99%
“…The complete tHsc70 amino acid sequence can be separated into two parts-the ATPase domain (1-385 aa) and the peptide-binding domain (386-646 aa) (Fig. 2) (Luan et al, 2010).…”
Section: Cloning and Sequence Analysis Of Turtle Thsc70mentioning
confidence: 99%
See 2 more Smart Citations
“…the marine harpacticoid Tigriopus japonicus (Rhee et al 2009). More generally, as underlined by Luan et al (2010), few reports exist on crustacean species.…”
Section: Introductionmentioning
confidence: 99%